Redox electrolytes in supercapacitors - Akinwolemiwa, Bamidele; Peng, Chuang; Chen, George Z. (Electrochemical Society, 2015)
Most methods for improving supercapacitor performance are based on developments of electrode materials to optimally exploit their storage mechanisms, namely electrical double layer capacitance and pseudocapacitance. In such cases, the electrolyte is supposed to be electrochemically as inert as possible so that a wide potential window can be achieved. Interestingly, in recent years, there has been a growing interest in the investigation of supercapacitors with an electrolyte that can offer redox activity. Such redox electrolytes have been shown to offer increased charge storage capacity, and possibly other benefits. There are however some confusions, for example, on the nature of contributions of the redox electrolyte to the increased storage capacity in comparison with pseudocapacitance, or by expression of the overall increased charge storage capacity as capacitance. This report intends to provide a brief but critical review on the pros and cons of the application of such redox electrolytes in supercapacitors, and to advocate development of the relevant research into a new electrochemical energy storage device in parallel with, but not the same as that of supercapacitors.